A handheld UV-C light-emitting diode decreases environmental contamination near the operative field - Rachael A. Turner; Roseann M. Johnson; Yasmin Yazdani-Farsad; Jessell Owens; Douglas A. Dennis; Jason M. Jennings (Antimicrobial Stewardship & Healthcare Epidemiology)
Abstract